PERAN VARIABEL MODERASI KOMPETENSI APARATUR TERHADAP PENGARUH ANTARA KEJELASAN SASARAN ANGGARAN DAN AKUNTABILITAS KINERJA PEMERINTAH DAERAH - Susanti, Susanti; Sarwono, Aris Eddy; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This research was conducted to determine the role of the moderatingvariable of apparatus competence on the influence betweenclarity of budgettargets and accountability of local government performance. The research usesprimary data from Koesioner answers that are distributed to governmentapparatus in Wonogiri District OPD. Sampling techniques using the purposivesampling method.The result of T count 6.927 with a P-value of 0.000 < 0.05 then Horejected means there is a significant influence on the clarity of the target budget(X1) to the performance accountability of the local government (Y). Results FCount of 47.978 with a P-value of 0.000 < 0.05 then this model is precise. Theresults of the R2 test obtained the Ajusted R square value of 0.317 means it can beknown that the influence given by the free variables is the target of the budgettargets (X1) to the bound variables that is the performance accountability of thelocal government (Y) has a real impact of 31% while the rest (100%-32%) = 68%are influenced by other factors outside The moderation variable regression testresults show P – value (significance) for a moderation variable of 0.022 < 0.05,so Ho is rejected, meaning that apparatus competency variable (X2) significantlymoderated the influence of the target clarity of budget (X1) towards the localgovernment's performance accountability (Y).